Thromboelastography demonstrates perioperative hypercoagulability in hepato-pancreato-biliary patients and supports routine administration of preoperative and early postoperative venous thromboembolism chemoprophylaxis. Issue 2 (February 2017) - Le, Anh-Thu; Harris, Jennifer W.; Maynard, Erin; Dineen, Sean P.; Tzeng, Ching-Wei D.
Abstract: Background: We hypothesized hepato-pancreato-biliary (HPB) surgery patients are more likely to be hypercoagulable than hypocoagulable, and that bleeding risks from VTE chemoprophylaxis are low. This study sought to use thromboelastography (TEG) to compare coagulation profiles with bleeding/thrombotic events in HPB patients receiving standardized perioperative chemoprophylaxis. Methods: Consecutive patients undergoing HPB resections by three surgeons at one institution (January 2014–December 2015) received preoperative and early postoperative VTE chemoprophylaxis and were evaluated with TEGs. Coagulation profiles were compared to bleeding/thrombotic events. Results: Of 87 total patients, 83 (95.4%) received preoperative chemoprophylaxis and 100% received it postoperatively. Median estimated blood loss was 190 ml. Only 2 (2.3%) patients received intraoperative transfusions. None required transfusions at 72-hours. Only 2 were transfused within 30 days. There was 1 (1.1%) 30-day VTE event. Of 83 preoperative TEGs, 29 (34.9%) were hypercoagulable and only 8 (9.6%) were hypocoagulable/fibrinolytic. Of 73 postoperative TEGs, 34 (46.6%) were hypercoagulable and just 8 (11.0%) were hypocoagulable/fibrinolytic. . Conclusion: With routine perioperative chemoprophylaxis, both VTE and bleeding events were negligible. Perioperative TEG revealed a considerable proportion (46.6%) of HPB patients were hypercoagulable. HPB patients can receive standardized preoperative/early postoperative VTE chemoprophylaxis with effective results and minimal concern for perioperative hemorrhage. Abstract : Synopsis: Thromboelastography revealed a considerable proportion of HPB patients were hypercoagulable perioperatively.